The Role of Vitamin D in Diabetes and Cardiovascular Disease: An Updated Review of the Literature. (20th October 2015) - Papandreou, Dimitrios; Hamid, Zujaja-Tul-Noor
Abstract : The dietary reference values for Vitamin D were set primarily considering its role in bone health, but with the discovery of Vitamin D receptors throughout body tissues, new links with other health conditions are now studied, such as for diabetes and cardiovascular diseases (CVD). This paper shall analyze and examine all new research studies carried out, especially in 2013–2015 regarding diabetes mellitus (DM) and cardiovascular diseases (CVD). Vast research has been carried out to establish strong relationship between Vitamin D serum levels, supplementation, diabetes, and CVD. However, the results from researches identified in this paper are disputable. Benefits of Vitamin D adequate levels were recognized from gestational period until later in disease development such as diabetes and/or CVD, but since not all studies are in agreement further investigation is suggested. Researches conducting large randomized controlled trials, exploring range of supplement doses, with variable baseline serum Vitamin D levels, and inclusion of array of associated parameters, are still required to conduct large-scale analysis and draw conclusion as a risk factor. Until then it is possible to conclude that maintenance of serum Vitamin D levels holds advantageous aspects in diabetic and cardiovascular conditions, and people should strive to attain them.